Cancellation of the Deed of Sale and Purchase Binding Made Before a Notary (Study in the West Lombok Regency Area) - Rahmat Agusfiyan; Lalu Husni; Salim HS (International Journal of Educational and Life Sciences, 2024)
The purpose of this study is to examine the progressive cancellation of APJB that took place in the West Lombok Regency area, as well as the legal ramifications of that cancellation when it was done in front of a notary. by applying techniques from empirical normative legal research. The research findings indicate that the notary's involvement in the gradual cancellation of the APJB in the West Lombok Regency area was passive; that is, the notary merely documents and interprets the parties' statements when they appear before him, so long as those statements do not violate any regulations. applicable laws, the conditions of the agreement in Civil Code Article 1320 and the terms that the notary specifies. As a result of the parties' agreement to terminate the agreement contained in the gradual APJB and declare it no longer valid, the engagement agreement is no longer binding on them. This is one of the legal ramifications of gradually canceling the APJB made before a notary. This cancellation makes it impossible to carry out the transfer of land and building rights or to continue with the progressive APJB.